Toxins and Cancer Therapy - Snook, Adam E. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Cancer has been a patient-specific and difficult-to-treat disease for decades, resulting in more deaths since 1900 than all other diseases except cardiovascular diseases. As societies around the world continue to shift towards an aging population, the social and economic burden created by cancer will only rise in the coming decades, necessitating continued improvement in our cancer therapies. Remarkably, in the late 1800s, bone surgeon William Coley serendipitously discovered that bacteria could be administered to patients as an effective (and sometimes toxic) form of cancer therapy known as "Coley's Toxins". His discoveries unknowingly led to two fields of cancer therapy that have been in development for decades and are now leading to significant improvements in therapy for cancer patients: immune-based and toxin-based therapies for cancer. Articles included here discuss the discoveries that emerged from Coley's Toxins that enable us to harness the immune system and microbial toxins to combat cancers, as oncology shifts from a field dominated by chemotherapy for most of the 20th century to biologic therapies that will dominate the 21st century.